2016
DOI: 10.4314/acsj.v24i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and field evaluation of liquid inoculants with native <i>Bradyrhizobial</i> strains for peanut production

Abstract: A critical process in the leguminous crops cycles is biological nitrogen fixation (BNF). Application of inoculants with N fixing bacteria is economically and environmentally favourable. The aim of this work was to select competitive native peanut microsymbionts, evaluate their survival in inoculant support and assess their impact on peanut (Arachis hypogaea L.) production under field conditions at Córdoba province in Argentina. The efficient N fixing Bradyrhizobium sp. J-81 and Bradyrhizobium sp. J-237, previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…e results obtained with BR 3267 relative to pod production in groundnut in this work are in agreement with the findings of Howarth et al [26], who reported a positive response of pod number and pod dry weight of groundnut following inoculation and attributed this to the presence of effective strains of rhizobia inoculated. e higher number of pod obtained by the application of 40 kg•N/ha compared with 20 kg•N/ha in cowpea agrees with the studies carried out by [27], who reported significant increases in pod number by increasing the amount of nitrogen applied.…”
Section: Pod Number and Pod Dry Weightsupporting
confidence: 90%
“…e results obtained with BR 3267 relative to pod production in groundnut in this work are in agreement with the findings of Howarth et al [26], who reported a positive response of pod number and pod dry weight of groundnut following inoculation and attributed this to the presence of effective strains of rhizobia inoculated. e higher number of pod obtained by the application of 40 kg•N/ha compared with 20 kg•N/ha in cowpea agrees with the studies carried out by [27], who reported significant increases in pod number by increasing the amount of nitrogen applied.…”
Section: Pod Number and Pod Dry Weightsupporting
confidence: 90%
“…Bradyrhizobium strains are the favorite micro-symbionts of peanut and large amounts of nitrogen can be fixed in trials under field conditions (Thies et al 1991;Valetti et al 2016). Within the Bradyrhizobium group, peanuts can nodulate with bacteria belonging to the B. elkanii clade, such as the commercial strain SEMIA 6144 or the clade B. japonicum, as several isolated strains from the semi-arid region of Brazil (Santos et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Peanut is able to associate efficiently with different rhizobial strains (Melo et al 2016), presenting higher efficiency the Bradyrhizobium genus (Valetti et al 2016;Santos et al 2017a). During the last years, some studies have been carried out in Brazil aiming to evaluate the biodiversity (Lyra et al 2013;Torres-Júnior et al 2014;Santos et al 2017a), the symbiotic efficiency (Torres-Júnior et al 2014;Santos et al 2017a, b), and the agronomic efficiency of new rhizobium strains (Sizenando et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The plants inoculated with the test isolate (23M) did not differ statistically neither, from the treatment that received inoculation with the strain SEMIA 6144, nor from noninoculated plants. According to Souza et al (2008), the biomass accumulation is a strong indicator of the nutritional status of the plants and has been one of the variables used in studies for selecting rhizobia isolates with potential for BNF (Marcondes et al, 2010;Torres Júnior et al, 2014;Valetti et al, 2016).…”
Section: Resultsmentioning
confidence: 99%